2013
DOI: 10.1039/c2cc36381j
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying alternating peptide synthesis by protease-catalyzed dipeptide oligomerization

Abstract: A unique route to perfectly alternating oligopeptides is described. First, AG-OEt was prepared by standard chemical coupling. Then, AG-OEt was converted by papain-catalysis in 30 s to (AG)(x) (80%-yield, x = 9.4 ± 0.3). Extension of this strategy to other alternating peptide compositions as well as the importance of selecting a protease and reaction conditions that avoid competing transamidation and hydrolysis reactions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…43 Alternating oligopeptides were synthesized by papain-mediated catalysis using the dipeptide monomer, alanine-glycine ethyl ester. 44 Papain-catalyzed oligomerization of L-lysine protected at the side chain with a tert-butoxycarbonyl or carboxybenzyl group ensures a higher yield and a simpler purification process owing to the precipitation-driven reaction derived from the hydrophobicity of the protected group. 45 Thus, papain is powerful, and the most-studied protease for chemoenzymatic synthesis of various types of peptides.…”
Section: Poly(amino Acid) As An Eco-friendly Materialsmentioning
confidence: 99%
“…43 Alternating oligopeptides were synthesized by papain-mediated catalysis using the dipeptide monomer, alanine-glycine ethyl ester. 44 Papain-catalyzed oligomerization of L-lysine protected at the side chain with a tert-butoxycarbonyl or carboxybenzyl group ensures a higher yield and a simpler purification process owing to the precipitation-driven reaction derived from the hydrophobicity of the protected group. 45 Thus, papain is powerful, and the most-studied protease for chemoenzymatic synthesis of various types of peptides.…”
Section: Poly(amino Acid) As An Eco-friendly Materialsmentioning
confidence: 99%
“…In contrast, CPDY is characterized as an exopeptidase that typically cleaves only amide bonds at C-termini. Therefore, CPDY-catalyzed polymerization avoids the hydrolysis of the polypeptide backbones of pre-existing polypeptides, resulting in efficient suppression of the broadening of the molecular weight distribution of the products that Methyl, [49,54] ethyl, [50][51][52][53][54][55][56] benzyl [54] Proteinase I, [49] papain (13)(14)(15)(16)(17)(18) [50][51][52][53][54][55][56] Glycine Methyl, [54] ethyl, [49,51,54,55] benzyl [54] Proteinase I, [49] papain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) [51,54,55] l-Leucine…”
Section: Materials and General Protocolsmentioning
confidence: 99%
“…Gross et al demonstrated that a dipeptide ester, l-alanylglycine ethyl ester (AlaGly-OEt), is a preferable substrate for papain and could be converted into a polypeptide with the strictly alternating sequence poly(Ala-alt-Gly) via chemoenzymatic polymerization. [51] On MALDI-TOF mass spectrometry, the polypeptides obtained from the AlaGly-OEt showed a series of peaks that corresponded to polypeptides containing stoichiometrically equivalent quantities of alternating l-alanine and glycine units. Thus, the use of dipeptide esters as monomers in chemoenzymatic polymerization can yield polypeptides with various types of alternating sequences.…”
Section: Hydrophobic Polypeptides For Structural Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the huge number of commercial enzymes, proteases are of great importance for their extensive applications in detergent, tanning, food processing, silk degumming, medical diagnosis, bioconversion, waste treatment, and peptide synthesis [2][3][4][5]. Currently, proteases have accounted for up to 60% of the total enzyme sales in the global market, in which alkaline proteases represent the largest portion [6].…”
Section: Introductionmentioning
confidence: 99%